2006
DOI: 10.2176/nmc.46.126
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Resolution of Diabetes Insipidus After Pituitary Stalk Sectioning During Surgery for Large Craniopharyngioma-Endocrinological Evaluation and Clinical Implications for Surgical Strategy-

Abstract: The mechanism of spontaneous resolution of diabetes insipidus (DI) was investigated after surgery for large craniopharyngioma. Twenty-two adult patients (mean age 48.9 years old), who underwent surgery via the anterior interhemispheric trans-lamina terminalis approach, were divided into three groups: Group I, the entire pituitary stalk was preserved (n = 2); Group II, the stalk was dissected distally from the tumor but ultimately sacrificed (n = 9); Group III, the stalk was not identified and was sacrificed (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 39 publications
(44 reference statements)
1
13
0
Order By: Relevance
“…Of these patients, 46 were dropped from the analysis since there were no follow-up data [7]. Other patients were excluded, including 5 patients who received immediate radiotherapy after surgery [5,15], two patients undergoing both transcranial surgery and gamma knife surgery before the second operation, one patient having transcranial surgery three times [16], 10 cases without ambiguous statistics [10], 16 patients with stereotactically guided cyst puncture, and/or biopsy and/or cerebrospinal fluid shunt placement [11], and 64 patients without pituitary stalk identification [11,12]. There were total 420 patients making up the study population, including 185 patients who had their pituitary stalk maintained and 235 patients who had their pituitary stalk removed.…”
Section: Search Results and Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these patients, 46 were dropped from the analysis since there were no follow-up data [7]. Other patients were excluded, including 5 patients who received immediate radiotherapy after surgery [5,15], two patients undergoing both transcranial surgery and gamma knife surgery before the second operation, one patient having transcranial surgery three times [16], 10 cases without ambiguous statistics [10], 16 patients with stereotactically guided cyst puncture, and/or biopsy and/or cerebrospinal fluid shunt placement [11], and 64 patients without pituitary stalk identification [11,12]. There were total 420 patients making up the study population, including 185 patients who had their pituitary stalk maintained and 235 patients who had their pituitary stalk removed.…”
Section: Search Results and Study Characteristicsmentioning
confidence: 99%
“…It was reported that the epithelial squamous cell nest of the pars tuberalis of the adenohypophysis is the major source of craniopharyngioma [8]. Therefore, the handling of the pituitary stalk during surgery is important but controversial [5][6][7][9][10][11][12][13][14][15][16]. Although several investigations showed that maintenance of the pituitary stalk could reduce the risk of altered endocrine function complication after surgery [6,[9][10][11], it was also frequently reported that the pituitary stalk might have lost its function due to the invasion of the craniopharyngioma [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Nishizawa et al [8] reported improvement in the symptoms of DI and reduced need for desmopressin among 4 of 22 adult patients 2.7 ± 1.3 years following resection of suprasellar craniopharyngioma. This case series is remarkable as none of the patients appeared to have DI preoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth preserving the pituitary stalk, even though it is very difficult in surgeries involving large craniopharingiomas. It may be sacrificed for total removal of the tumour 17. The resultant hypothalamic pituitary hypofunction may require cortisol and thyroid hormone replacement therapy 17.…”
Section: Discussionmentioning
confidence: 99%
“…It may be sacrificed for total removal of the tumour 17. The resultant hypothalamic pituitary hypofunction may require cortisol and thyroid hormone replacement therapy 17. Patients may also develop DI and thus require nasal administration of desmopressin 17…”
Section: Discussionmentioning
confidence: 99%